Fluid Mechanics for Chemical Engineering. - Mory, Mathieu (London : Wiley, 2013)
The book aims at providing to master and PhD students the basic knowledge in fluid mechanics for chemical engineers. Applications to mixing and reaction and to mechanical separation processes are addressed. The first part of the book presents the principles of fluid mechanics used by chemical engineers, with a focus on global theorems for describing the behavior of hydraulic systems. The second part deals with turbulence and its application for stirring, mixing and chemical reaction. The third part addresses mechanical separation processes by considering the dynamics of particles in a fl.
4.2. Steady-state flows in straight pipes: regular head loss4.3. Turbulence in a pipe and velocity profile of the flow; 4.4. Singular head losses; 4.5. Notions on cavitation; 4.6. Application exercises; Exercise 4.I: Regular head loss measurement and flow rate in a pipe; Exercise 4. II: Head loss and cavitation in a hydraulic circuit; Exercise 4. III: Ventilation of a road tunnel; Exercise 4. IV: Sizing a network of heating pipes; Exercise 4.V: Head, flow rate, and output of a hydroelectric power plant; 4.7. Bibliography; Chapter 5. Pumps; 5.1. Centrifugal pumps; 5.1.1. Operating principle.
Print version record.
5.1.2. Similarity laws and head/capacity curves.
Keywords: Chemical processes; Fluid dynamics; Processos químics; Dinàmica de fluids; SCIENCE -- Chemistry -- Industrial & Technical; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Chemical processes; Fluid dynamics; Llibres electrònics; Electronic books